PREVALENCE OF DOMESTIC ACCIDENTS AND PREVENTIVE PRACTICE AMONG WOMEN OF CHILDBEARING IN IKORODU LOCAL GOVERNMENT AREA, LAGOS STATE - WALIU BABATUNDE OGUNBAMOWO; BODUNRIN OLUGBENGA ADEYEMI; LIGALI LATEEFAT ABIODUN; ASHON DANIEL OLUWATOBI (International Studies Journal)
The study examined the prevalence of domestic accidents and preventive practice among women of childbearing age in Ikorodu Local Government Area, Lagos state. Two research questions and hypotheses were postulated, and it employed a descriptive research design. Th study consisted of three hundred women of childbearing age in, Ikorodu Local Government Area, Lagos state and utilized a self-developed questionnaire titled Domestic Accident Questionnaire(DAQ) to collect data. Data collected were analyzed using descriptive statistical tool of frequency counts and percentage. While inferential statistics of Chi-square was used to analyze all formulated hypotheses. The findings show that, there was significant relationship between prevalence of falls and preventive practice of domestic accidents among women of childbearing age in Ikorodu, Lagos Stateand there is no significant relationship between prevalence of burns and preventive practice of domestic accidents among women of childbearing in Ikorodu, Lagos State. Specifically, the results showed that that there was significant relationship between prevalence of falls and preventive practice of domestic among women of childbearing age in Ikorodu, Lagos State (X2=128.24, p= 0.000<0.05) and there is no significant relationship between prevalence of burns and preventive practice of domestic accidents among women of childbearing in Ikorodu, Lagos State (X2=73.65, p= 0.079>0.05). The study recommends that Government agencies should work together to coordinate and implement fall prevention efforts, this could involve sharing information and resources, and developing comprehensive programs that address all aspects of fall prevention. Healthcare providers should be educated about the importance of fall prevention and the strategies that can be used to reduce the risk of falls, this could be done through continuing education programs and through the inclusion of fall prevention in health education curriculum in all schools.